PENGARUH MOTIVASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. ANGKASA PURA II KANTOR CABANG UTAMA BANDARA UDARA INTERNASIONAL SOEKARNO-HATTA TANGERANG BANTEN: (Studi Kasus Pada Unit Finance & Human Resources) - Agustina Solihati, Vina; Latuconsina, Hudaya; Ahmad, Ahmad (DESANTA (Indonesian of Interdisciplinary Journal), 2025)
This study aims to determine the effect of motivation, compensation, and work environment partially and simultaneously on the performance of employees of PT. Angkasa Pura II Main Branch Office of Soekarno-Hatta International Airport in the Finance & Human Resources Unit. In collecting this data, it was obtained using primary data, secondary data, and questionnaires. The population in this study were employees of the Finance & Human Resources Unit of PT. Angkasa Pura II Main Branch Office of Soekarno-Hatta International Airport, with a sample of 80 respondents. This research uses quantitative research methods with saturated sampling techniques and uses multiple linear regression analysis techniques. The results of this study indicate that the variables of motivation, compensation and work environment simultaneously have a positive and significant effect on employee performance.